Direct antagonism and biocontrol of tomato soft rot using prokaryotes - Barra, Victor Rafael; Romeiro, Reginaldo da Silva; Garcia, Flávio Augusto de Oliveira; Moura, Andréa Bittencourt; Silva, Harllen Sandro Alves; Mendonça, Henrique Lopes; Halfeld-Vieira, Bernardo de Almeida (Pesquisa Agropecuaria Brasileira, 2010)
This work aimed to evaluate prokaryotes to provide direct antagonism and biocontrol of tomato soft rot (Pectobacterium carotovorum subsp. carotovorum). Forty-five bacterial isolates previously selected for biological control of several tomato (Lycopersicon esculentum Mill.) diseases were evaluated using an antibiosis test. 'Santa Clara' tomato seeds were inoculated with potential antagonist isolates and transplanted to a soil infested with the pathogen, in two asseys, at a propagule concentration of OD540 0.45 and 0.65. Antagonists UFV-0005, UFV-043, UFV-BF112, and UFV-0006 protected tomato plants disease.